Gallery of Prosthodontic Procedural Technique Videos (Out of Print) - Ranier Adarve (Association of American Medical Colleges, 2009)
Abstract This website contains a collection of videos of procedures and techniques in preclinical and fixed prosthodontics. In this gallery, typically lengthy dental procedures are broken into smaller segments and recorded in short video clips to enable learners to watch and focus on every step of these complex skills. The video interface also provides learners with the ability to rewind, fast-forward, and replay video clips at their own pace, giving them the opportunity to rehearse and master a skill. The gallery of videos is currently utilized by first-year dental students at the University of Minnesota School of Dentistry. Students tend to watch the videos repeatedly prior to performing a procedure. Videos provide a useful overview to the learners and a useful teaching tool for the faculty.